2021
DOI: 10.1038/s41598-021-94124-5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc status in attention-deficit/hyperactivity disorder: a systematic review and meta-analysis of observational studies

Abstract: Previous studies regarding the zinc status in attention-deficit/hyperactivity disorder (ADHD) yielded inconsistent results. Thus, the present meta-analysis was aimed to estimate the association between hair and serum/plasma zinc levels and ADHD. Online databases of Medline, EMBASE, and Scopus were searched up to October 2020 with no limitation in time and language. Weighted mean differences (WMDs) of hair and serum/plasma zinc levels were calculated using a random-effects model. Overall, 22 articles with 1280… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
(75 reference statements)
0
4
0
1
Order By: Relevance
“…In contrast, a review from 2018 concluded that low serum iron levels were associated with ADHD [58]. There was no difference in zinc levels in blood, serum, plasma [59] or hair between children and adolescents with ADHD and healthy controls [60].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a review from 2018 concluded that low serum iron levels were associated with ADHD [58]. There was no difference in zinc levels in blood, serum, plasma [59] or hair between children and adolescents with ADHD and healthy controls [60].…”
Section: Resultsmentioning
confidence: 99%
“…However, zinc may be widely involved in the pathophysiology of other mental disorders due to its role in numerous biological processes 20 . Some meta-analyses have shown that lower zinc levels were also observed in people with depression 39 and neurodevelopmental disorders, including autism spectrum disorder 40 and attention-deficit hyperactivity disorder 41 . Thus, further studies in adolescents will be required to investigate the relationship between lower zinc levels and the risk of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency has been suggested to increase the risk of ADHD, while sufficient zinc supply is thought to improve ADHD symptoms. Since various studies regarding the zinc status in ADHD yielded inconsistent results, a recent systematic review and meta-analysis attempted to estimate the association between ADHD and serum/plasma and hair zinc concentrations [ 29 ]. This meta-analysis including 22 studies (1280 individuals with ADHD and 1200 controls) found no statistically significant difference in hair and serum/plasma zinc levels between people with ADHD and controls.…”
Section: Zincmentioning
confidence: 99%
“…This meta-analysis including 22 studies (1280 individuals with ADHD and 1200 controls) found no statistically significant difference in hair and serum/plasma zinc levels between people with ADHD and controls. Sensitivity analysis in studies examining circulating levels of zinc showed that the exclusion of one study changed the overall effect, with circulating zinc levels being significantly lower in individuals with ADHD in comparison with healthy controls [ 29 ]. Further well-designed studies need to clarify the pathophysiological role of zinc in ADHD.…”
Section: Zincmentioning
confidence: 99%